The Correlation Between Lead Level and Hemoglobin, Hematocrit, Cystatin C Serum, SGOT and SGPT Levels of Car Paint Workers - Tutuarima, Jemmy (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
An industrial upgrading will result in a variety of wastes being released into the environment that ultimately impact on public health. One of the hazardous wastes is Pb. The purpose of this research is to know the correlation of Pb in blood to hb level, hematocrit, serum Cystatin C, SGOT and SGPT serum and health complaints on car paint workers of workshop in Rungkut Sub-district Surabaya. This research was an observational research with cross sectional design. Sampling method using simple random sampling. The study sample consisted of 24 people. The result of statistical test shows that there is a correlation of Pb exposure in air to blood Pb level with contribution amount 80% (r = 0.527; p = 0.008). Decreased levels of hemoglobin, hematocrit, elevated serum Cystatin C levels, SGOT and SGPT serum and health complaints of nerve and liver function were associated with blood levels of Pb with p <0.05. Based on the results of this study it can be concluded that the exposure of Pb in the air has a relationship to the increase of Pb levels in the blood of car paint workers of workshop in Rungkut Sub-district, Surabaya.  Keywords: Paint workers of workshop, Pb in air, PB in blood, Hemoglobin, Hematrocrit